1994
DOI: 10.1111/j.1440-1681.1994.tb02445.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atrial Natriuretic Peptide on Cellular Element Concentrations in Rat Proximal Tubules: Evidence for Inhibition of the Sodium Pump

Abstract: 1. In order to further define the action of atrial natriuretic peptide (ANP) on proximal tubular (PT) transport, combined clearance and electron microprobe X-ray (EMPX) experiments were performed on five male Wistar rats infused with ANP (0.16 nmol/kg per h) and nine control animals. 2. Electron microprobe X-ray analysis of PT cell electrolytes (mmol/kg wet weight) revealed a similar [Na]i in both the control and ANP treated groups (16.4 +/- 0.4 vs 16.5 +/- 0.4; P = 0.894). [Cl]i was lower in the ANP treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…However, the cGMP increase in these collecting duct cells is not mediated by natriuretic peptides (Schlatter et al 1996). An inhibitory effect of natriuretic peptides on Na¤-coupled substrate transport in the proximal tubule was postulated previously (Hammond et al 1985;Harris et al 1987;Reddy et al 1994;Eitle et al 1998;Jacobs et al 1999). Besides the possibility of a direct effect of ANP on Na¤-coupled transport proteins, a second possibility would be a decrease in the driving force for Na¤-coupled transport by inhibition of K¤ conductances.…”
Section: Discussionmentioning
confidence: 88%
“…However, the cGMP increase in these collecting duct cells is not mediated by natriuretic peptides (Schlatter et al 1996). An inhibitory effect of natriuretic peptides on Na¤-coupled substrate transport in the proximal tubule was postulated previously (Hammond et al 1985;Harris et al 1987;Reddy et al 1994;Eitle et al 1998;Jacobs et al 1999). Besides the possibility of a direct effect of ANP on Na¤-coupled transport proteins, a second possibility would be a decrease in the driving force for Na¤-coupled transport by inhibition of K¤ conductances.…”
Section: Discussionmentioning
confidence: 88%
“…Reddy et 01. 73 found cell swelling in response to A N F in proximal tubule cells from rat kidneys examined using electron microprobe X-ray analysis and concluded that A N F directly inhibits the sodium pump. A second mechanism involves a cGMP-activated CI-channel found in cultured rat proximal convoluted tubule cells74 that could mediate the action of ANF by allowing CI-to leave the cells and thus reduce the lumen positive driving force for Na* reabsorption.…”
Section: Atrial Natriuretic Factormentioning
confidence: 99%